2021
DOI: 10.1101/2021.03.11.435004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved BAH module within mammalian BAHD1 connects H3K27me3 to Polycomb gene silencing

Abstract: Trimethylation of histone H3 lysine 27 (H3K27me3) is important for gene silencing and imprinting, (epi)genome organization and organismal development. In a prevalent model, the functional readout of H3K27me3 in mammalian cells is achieved through the H3K27me3-recognizing chromodomain harbored within the chromobox (CBX) component of canonical Polycomb repressive complex 1 (cPRC1), which induces chromatin compaction and gene repression. Here, we report that binding of H3K27me3 by a Bromo Adjacent Homology (BAH) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…It has previously been shown that the BAH domain from BAHD1 recognises H3 histone tails bearing a K27me3 modification ( 10 ). We confirmed this interaction using a fluorescence anisotropy assay (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has previously been shown that the BAH domain from BAHD1 recognises H3 histone tails bearing a K27me3 modification ( 10 ). We confirmed this interaction using a fluorescence anisotropy assay (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-targeted HDAC complexes typically contain domains or sequence motifs, or accessory proteins that mediate interaction with chromatin ( 31 ). The MIER complex has been reported to associate with the chromodomain protein CDYL and the BAH domain protein BAHD1 ( 10, 13, 32 ). When we co-expressed MIER1 with HDAC1 and the BAH domain from BAHD1 we found that the endogenous protein C1QBP co-purified with the complex in apparently stoichiometric amounts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histone methylation is an important epigenetic modification that can regulate gene expression and mainly occurs at the lysine residues of histones [15,16]. The trimethylation of histone H3 lysine 27 (H3K27me3) modification is mainly regulated dynamically by intracellular lysine methyltransferases and demethylases [17,18].…”
Section: Introductionmentioning
confidence: 99%